Differentiated Ionic Electroresponse of Asymmetric Bio‐Hydrogels with Unremitting Power Output. Issue 12 (12th February 2023) - Pan, Xinglong; Jin, Yakang; Zhou, Yi; Wang, Xiao‐Qiao; Lu, Wanheng; He, Jiaqing; Ho, Ghim Wei
Abstract: Cytomembranes with efficient ionic selectivity and energy circulation, essential for biological activities in multicellular organisms, are a source of inspiration for man‐made biomedical devices. However, current man‐made soft systems mainly imitate simple and passive cytomembranes behaviors, restrained by the grand challenge that lies at the meeting point of synchronous engineering of both (dynamic) ionic selectivity and (passive) transcellular‐like potential in one structure. Here a dynamically differentiated ionic electroresponse and passive incessant power output of an asymmetric bio‐hydrogel constructed using a simple self‐propagative flow approach are reported. The unprecedented freely formed p and n analogue hydrogels yield a transcellular‐like potential (110–200 mV) in response to diverse stimuli—where the cathode or anode is capable of perceivable electroresponse to water and/or salt media, respectively. A single hydrogel can generate an output power density of 135–190 mW m −2 superior to most bio‐inspired soft and/or green power sources. The scalable manufacturing and proof‐of‐concept demonstration elucidate the feasibility of mobilizing passive and dynamic behaviors in one structure. This work has the potential for realizing high‐performance soft power sources in parallel to electrostimulation for neural excitation/inhibition, extending into the previously inaccessible region of biomedical applications. Abstract : Cytomembranes with efficient ionic selectivity and energy circulation, essential for biological activities in multicellular organisms, are a source of inspiration for artificially engineered systems. The reported, unprecedented freely formed p and n analogue hydrogels yield a perceivable transcellular‐like potential of 110–200 mV and power density of 135–190 mW m −2 in response to diverse stimuli.